Development of Domino Card Media Based on QR Code to Improve Numeracy Skills of Grade 3 Students of UPT SDN Tumpang 02 Blitar Regency - Alina, Irfama; Alfi, Cindya; Fatih, Mohamad (FKIP-Universitas Riau, 2024)
This study aims to determine the validity, feasibility, and attractiveness of the development of domino card media based on QR codes for fractional material and to determine whether there is an increase in the numeracy skills of grade 3 students of UPT SDN Tumpang 02 Blitar Regency using the development of domino card media based on QR codes for fractional material. The method used in this study is the Research and Development (R&D) research method or research and development using the Borg and Gall research model consisting of 10 steps. This study uses data collection techniques in the form of questionnaires and tests. Based on the results of the study, it can be seen that the validity of the domino card media based on QR codes for fractional material obtained a total percentage of 94.84% and is included in the very valid category. The feasibility of the domino card media based on QR codes for fractional material obtained a final value of 84.375% and is included in the very feasible category with revisions. While the attractiveness of the domino card media based on QR codes for fractional material obtained a final value of 99.38% with a very interesting category. In addition, the results obtained from the n-gain value obtained a value of 0.87 with a high category, which means that there is a high influence in improving students' numeracy skills using the development of domino card media based on QR codes for fractional material.